THE STIMULATION OF GONAD MATURITY OF ASIAN REDTAIL CATFISH Hemibagrus nemurus (Valenciennes, 1840) THROUGH INDUCTION OF OOCYTE DEVELOPER (Oodev) HORMONE - Devika Kharisma Putri; Tarsim Tarsim; Deny Sapto Chondro Utomo; Indra Gumay Yudha (University of Lampung, 2019)
Oodev hormone application has been applied to stimulate gonadal maturity so that fish fry could be available outside the spawning season. This research aimed to study the effect of Oodev hormone on the gonadal maturity of asian redtail catfish Hemibagrus nemurus (Valenciennes, 1840). This research method used a completely randomized design (CRD) with 4 doses treatments, i.e 0, 0,25, 0,50, 1,00 ml/kg. A total of 8 fish were used as replications for each treatment. The parameters measured were the gonado somatic index (GSI) and egg diameter. The results showed that the effect of Oodev hormone on GSI and egg diameter was significantly different (P<0.05). A higher Oodev hormone dose caused an increase of GSI and egg diameter size. The recommended Oodev dose for application is 1 ml/kg.